Buffeting response evaluation of slender linear structures considering the influence of the aspect ratio on the scale effect. (21st July 2022) - Su, Yi; Di, Jin; Zuo, Tingzhong; Li, Shaopeng; Qin, Fengjiang
Highlights: A prediction method considering the influence of the scale effect for the buffeting response of slender linear structures is proposed. The influence of the structural aspect ratio on the scale effect of the buffeting response of slender linear structures is investigated. A reasonable sectional model vibration test technique used to predict the buffeting response of slender linear structures is provided. Abstract: Scale effect has a non-negligible influence on the buffeting response of a slender linear structure. Among them, the effect of the ratio of the turbulence integral scale to the structure width is widely recognised. However, past research neglected the role of the aspect ratio, and the experiments did not accurately simulate the turbulence characteristics of the atmospheric boundary layer. This let to distortions in the prediction results of the structural buffeting response obtained based on wind tunnel tests. Based on the recent scholars' understanding of the effect of the aspect ratio on aerodynamic admittance and the concept of integrated transfer function, a method for predicting the buffeting response of slender linear structures based on the three-dimensional two-wavenumber buffeting analysis theory is proposed in this paper. A calculating example of a slender linear structure with an airfoil section is designed. The sectional model vibration test is used to investigate the effect of the two important influencing parameters of the scale effect, especially the aspect ratio, on the integrated transfer function and buffeting response. The prediction value of the actual structural buffeting response based on an integrated transfer function identified through the sectional model vibration test is compared with the theoretical calculation value, and it verifies the accuracy and effectiveness of the proposed method. Meanwhile, a problem existing in the test methods for identifying the required aerodynamic parameters in the theoretical calculation of the buffeting response of slender linear structures is identified, and an effective solution is provided.